Beethoven's Centennial Celebration in Salzburg organized by the Salzburg Festival Hall Community and the International Mozarteum Foundation March-August 1927 - Internationale Stiftung Mozarteum Salzburg:::Creator::::::::::::; Salzburger Festspiele:::Contributor:::::::::::: (Salzburg; Austria, 2020)
Program for a performance of Beethoven's Ninth Symphony directed by Bernhard Paumgartner, March 22, 1927, with text of Schiller's Ode "An die Freude" on verso.